Ordering Africa : anthropology, European imperialism and the politics of knowledge. - Tilley, Helen; Gordon, Robert J. (Studies in imperialism, 2007)
African research played a major role in transforming the discipline of anthropology in the twentieth century. Ethnographic studies, in turn, had significant effects on the way imperial powers in Africa approached subject peoples.